The CO2 reduction potential for the European industry via direct electrification of heat supply (power-to-heat) - Silvia Madeddu; Falko Ueckerdt; Michaja Pehl; Juergen Peterseim; Michael Lord; Karthik Ajith Kumar; Christoph Krüger; Gunnar Luderer (Environmental Research Letters, 2020)
The decarbonisation of industry is a bottleneck for the EU’s 2050 target of climate neutrality. Replacing fossil fuels with low-carbon electricity is at the core of this challenge; however, the aggregate electrification potential and resulting system-wide CO _2 reductions for diverse industrial processes are unknown. Here, we present the results from a comprehensive bottom-up analysis of the energy use in 11 industrial sectors (accounting for 92% of Europe’s industry CO _2 emissions), and estimate the technological potential for industry electrification in three stages. Seventy-eight per cent of the energy demand is electrifiable with technologies that are already established, while 99% electrification can be achieved with the addition of technologies currently under development. Such a deep electrification reduces CO _2 emissions already based on the carbon intensity of today’s electricity (∼300 gCO _2 kWh _el ^−1 ). With an increasing decarbonisation of the power sector IEA: 12 gCO _2 kWh _el ^−1 in 2050), electrification could cut CO _2 emissions by 78%, and almost entirely abate the energy-related CO _2 emissions, reducing the industry bottleneck to only residual process emissions. Despite its decarbonisation potential, the extent to which direct electrification will be deployed in industry remains uncertain and depends on the relative cost of electric technologies compared to other low-carbon options.